I'm doing expressions: and i know that the first term in the brackets you multiply that by the closesed whole number immediatly beside it, and stuff!
(example: 2(s + 4)=2s + 8)
but for this: 4(9 - y) what would i do?
a*(b + c) = a*b + a*c
(a + b)*c = a*c + b*c
(For technical reasons there is a difference between the two statements. If a, b, and c are real numbers and "+" and "*" are ordinary addition/subtraction and multiplication respectively then the two statements are identical.)
In your case:
4(9 - y) = 4(9 + (-y)) = 4*9 + 4*(-y) = 4*9 - 4*y = 36 - 4y